Early lumbar puncture and risk of intraventricular hemorrhage in very low birth weight infants. (February 2018) - Testoni, Daniela; Hornik, Christoph P.; Guinsburg, Ruth; Clark, Reese H.; Greenberg, Rachel G.; Benjamin, Daniel K.; Smith, P. Brian
Abstract: Background: Lumbar puncture (LP) is the gold standard for diagnosing meningitis; however it is unknown whether early LP (≤ 3 days of life) is associated with increased risk of intraventricular hemorrhage (IVH) in very low birth weight (VLBW) infants. Objective: To determine whether early LP in VLBW infants is associated with severe IVH. Methods: VLBW infants from a cohort of 1, 158, 789 infants discharged from 382 neonatal intensive care units (1997–2015) were enrolled. Exclusion criteria: infants with major congenital anomalies, outborns, died/transferred prior to day of life 3, and those who had an LP performed only after day of life 3. Logistic regression was used to determine the association between early LP and the incidence of severe IVH (IVH grades 3/4) by 28 days of life for each day of life from day 0 (birth) to day 3, adjusting for clinical covariates. Results: 106, 461 infants were included: 754 received an LP on Day-0, 640 on Day-1, 559 on Day-2 and 483 on Day-3. Severe IVH occurred in 4% (4130/104, 025) of the infants in the no LP group and 9% (217/2436) of the LP group. Severe IVH was higher for infants with early LP: adjusted OR (95% confidence interval) = 2.64 (1.96–3.54) on Day-0; 2.21 (1.61–3.04) on Day-1; 1.55 (1.03–2.34) on Day-2; and 2.25 (1.50–3.38) on Day-3. Conclusions: Early LP was associated with severe IVH in VLBW infants by 28 days of life. LP is either a surrogate for an unrecognized factor or is itself associated with an increased risk of IVH. Highlights: There is an important practice variation among sites: 0% to 85% of infants received early lumbar puncture (LP). Early lumbar puncture was associated with severe intraventricular hemorrhage in VLBW infants by 28 days of life. LP is either a surrogate for an unrecognized factor or is associated with an increased risk of intraventricular hemorrhage.